SOME OPINIONS ABOUT THE PSYCHOLOGICAL NATURE OF WILLPOWER - Baramidze , Nodar (Georgian Psychological Journal, 2022)
According to the author’s opinion D. Uznadze’s and Sh. Chkhartishvili’s judgments about the willpower, complement each other in a certain way. It is true, that Uznadze connected the phenom- enological side of the willpower act to the “I want” feeling and for Chkhatarashvili it turned out to be the feeling “I must”, but on bases of peculiar analyses the author thinks that in any structure of behaviour the both feelings are present. In particular, the feeling “I must” dominates at the stage of decision-making and the feeling “I want” reveals as the desire to realize the decision willpower. It appears by the way of feeling sensual and to comply with the decision made by justiﬁcation, also the way of fulﬁlling. Another feeling may be instant and/or long duration, which constantly changes by inﬂuence of inner and outside motivational station and it may be suppress as well. According to this phenomenal side of conduct is changeable too.